The role of active herpesvirus infection in the formation of atopic dermatitis and psoriasis - T. V. Solomay; T. A. Semenenko; S. L. Vedunova; E. I. Isaeva; E. N. Vetrova; N. V. Karazhas (Сибирский научный медицинский журнал)
The results of previous studies suggest the involvement of herpes viruses in the development of atopic dermatitis and psoriasis, but there is no convincing evidence. Aim of the study was to evaluate the role of active herpesvirus infection in exacerbation of atopic dermatitis and psoriasis. Material and methods. The analysis of the incidence of infectious mononucleosis, genital herpes, cytomegalovirus infection, skin and subcutaneous tissue diseases, atopic dermatitis, psoriasis in Russia in 2000–2020 was carried out. 92 blood donors and 97 patients with skin and subcutaneous tissue diseases (44 with atopic dermatitis and 53 with psoriasis) were examined for the presence of immunoglobulins M and G to herpes simplex viruses (HSV1,2), Epstein-Barr (EBV), cytomegalovirus (CMV), human herpes type 6 (HНV6). Results and discussion. A significant strong direct correlation was revealed between the incidence of genital herpes and diseases of the skin and subcutaneous tissue (p = 0.85), atopic dermatitis (p = 0.85); infectious mononucleosis and psoriasis (p = 0.85). The frequency of detection of IgM to HSV1,2, in total, IgG EA and IgM VCA EBV in the group of patients is significantly higher than in donors (p < 0.05). In patients with atopic dermatitis, IgM to HSV1 were detected significantly more often than in individuals with psoriasis, and markers of active EBV infection were significantly less common. The presence of IgM HSV-1 statistically significantly increases the incidence of atopic dermatitis (relative risk (RR) = 2.3, 95 % confidence interval (95 % CI) 1.6–3.3)), IgM VCA and IgG EA EBV – the incidence of psoriasis (RR = 2.3, 95 % CI 1.5–3.3). Conclusions. It has been shown for the first time that active HSV1,2 infection is a trigger factor for the development of atopic dermatitis, EBV infection is psoriasis.